Customer experience design: a case study in the cultural sector. (21st August 2017) - Ponsignon, Frederic; Durrieu, Francois; Bouzdine-Chameeva, Tatiana
Abstract : Purpose: The purpose of this paper is to explore the experience design phenomenon in the cultural sector. Specifically, it purports to articulate a set of design characteristics that support the alignment between an organisation's design intention (i.e. intended experience) and the actual experience of customers (i.e. realised experience). Design/methodology/approach: A single case study approach is adopted to explore the phenomenon from both the provider and customer perspectives simultaneously. A range of qualitative data, including 42 interviews with managers and customers as well as voluminous documentary evidence, are collected. Provider and customer data are analysed independently using a rigorous inductive analytical process to generate experience design themes and to assess possible gaps between intended and realised experience. Findings: The findings reveal the design characteristics of touchpoints and the overall customer journey, which constitute the core experience, as well as the design characteristics of the physical and social environment, which support the realisation of the core experience, in a cultural context. Research limitations/implications: Limitations include difficulties in generalising the findings from a single case and in claiming that the set of design characteristics identified is exhaustive. Practical implications: The paper makes several recommendations that are useful and relevant for customer experience practitioners in the cultural sector. Originality/value: The paper's contribution is to provide novel empirical insights into the four experience design areas of touchpoints, journey, physical elements and social elements in an experience-centric cultural context. On that basis, a conceptual framework for experience design in the cultural context is proposed.